2009
DOI: 10.2353/ajpath.2009.080539
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Pancreatic Islets Are Resistant to Indoleamine 2,3 Dioxygenase-Induced General Control Nonderepressible-2 Kinase Stress Pathway and Maintain Normal Viability and Function

Abstract: Islet transplantation is a promising treatment for diabetes. However, it faces several challenges including requirement of systemic immunosuppression. Indoleamine 2,3-dioxygenase (IDO), a tryptophan degrading enzyme, is a potent immunomodulatory factor. Local expression of IDO in bystander fibroblasts suppresses islet allogeneic immune response in vitro. The aim of the present study was to investigate the impact of IDO on viability and function of mouse islets embedded within IDO-expressing fibroblastpopulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 55 publications
4
21
0
Order By: Relevance
“…Compared to other cell types, T cells appear particularly sensitive to the effects of GCN2 [106]. However, like many signaling pathways, GCN2 elicits different downstream cellular responses in different subsets of T cells [104].…”
Section: Effects Of Ido Mediated Via Gcn2-kinase and Kynurenine-pathwmentioning
confidence: 99%
“…Compared to other cell types, T cells appear particularly sensitive to the effects of GCN2 [106]. However, like many signaling pathways, GCN2 elicits different downstream cellular responses in different subsets of T cells [104].…”
Section: Effects Of Ido Mediated Via Gcn2-kinase and Kynurenine-pathwmentioning
confidence: 99%
“…Forouzandeh et al studies [23] also revealed that selective activation of GCN2 kinase pathway in response to IDO induced tryptophan deficiency is responsible for T cell apoptosis. Further studies by our group [8], [24], [25] demonstrated that IDO expression by bystander fibroblasts can prevent cellular and humoral allo-immune responses against islet allotransplant without having any adverse effect on viability and functionality of the graft. Although these data support the feasibility of using local IDO expression as an alternative for systemic immunosuppressive treatments following allotransplantation, there are limited reports [26], [27] that have examined the use of IDO expression for graft protection following xenotransplantation.…”
Section: Introductionmentioning
confidence: 98%
“…13 Indoleamine 2,3-dioxygenase generates a microenvironment, low in tryptophan and rich in kynurenine metabolites, that is selectively toxic to T-cells, whereas allogeneic islets remain intact. 13,14 Using the FPCM, we demonstrated that transient adenoviral transduction of IDO in fibroblasts prolongs the survival of allogeneic islets embedded within this scaffold up to 6 weeks. 15 The purpose of this study was, therefore, to overcome 2 main difficulties that we encountered in our previous research: (i) the gradual biodegradation and contractibility of FPCM that could compromise long-term transplant outcome 8 ; and (ii) the transient IDO expression in fibroblasts, limiting the period of graft survival.…”
mentioning
confidence: 94%